'I felt closed in and like I couldn't breathe': A qualitative study exploring the mainstream educational experiences of autistic young people. (September 2018) - Goodall, Craig
Background and aim: More autistic young people are being educated in mainstream schools. While existing research suggests that the outcomes of mainstream inclusion are mixed for autistic young people, few studies have examined their views and experiences directly. This article discusses the educational experiences of 12 autistic young people (aged 11–17 years) from their perspectives and how education could be improved to better support the others with autism. Methods: A flexible qualitative participatory approach was used which incorporated a range of methods, including individual semi-structured interviews, diamond ranking activities and draw-and-tell activities. A Children's Research Advisory Group (CRAG) advised on the methods used and matters to be explored. Results: The young people offered insights into how education has been for them in mainstream school, mostly negative, but with islets of positive experience. Several described themselves as being socially, emotionally and physically isolated from peers, with loneliness and bullying experienced by some. Participants felt unsupported and misunderstood by teachers within a social and sensory environment that was antithetical to their needs. Some spoke of the dread they felt before and during school and the negative impact their experiences in mainstream has had on their wellbeing. Many participants suggested simple strategies and curriculum adaptations that they felt would have helped make their time at mainstream more successful. These include having more breaks, smaller class sizes, less homework, instructions broken down, safe places to use when anxious and teachers who listen to their concerns and take account of their needs. In short they want to be understood, supported and included. Conclusions: There exists scope to better support autistic young people in mainstream education, as evidenced by the literature and the participants in this paper. The participants demonstrate that mainstream is not working for all and that changes, such as smaller class sizes, flexible pedagogy and understanding could improve education for autistic learners. Implications: Autistic young people can and should be central to the discussion on school improvement. They also show that being academically able for mainstream school should not be the only aspect when deciding on the suitability of mainstream school for meeting their needs. The young person's social and emotional wellbeing must be considered to ensure they can flourish, and not flounder.